Kajian Biblika 1korintus 15: 1-11 Bagi Pemahaman Iman Kristen Tentang Kebangkitan Yesus Kristus - Moses Wibowo; Tony Salurante (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
The doctrine of the resurrection of Christ is one of the foundations in Christianity. But the foundation of this faith continues to be challenged and attacked. One of the attacks came from Rudolf Bultmann, who believed that the resurrection of Jesus Christ was only a spiritual awakening and not even an objective historical reality. In the Indonesian context, there is a tradition called